Unexplained early neurological deterioration after endovascular treatment for acute large vessel occlusion: incidence, predictors, and clinical impact: Data from ANGEL-ACT registry. (30th September 2021) - Sun, Dapeng; Tong, Xu; Huo, Xiaochuan; Jia, Baixue; Raynald,; Wang, Anxin; Ma, Gaoting; Ma, Ning; Gao, Feng; Mo, Dapeng; Song, Ligang; Sun, Xuan; et al.
Abstract : Background: Early neurological deterioration (END) may occur in some patients with acute large vessel occlusion (LVO) undergoing endovascular treatment (EVT). Despite several clear causes of END, such as symptomatic intracranial hemorrhage, failure of recanalization, and intraprocedure complications, a particular END, termed unexplained END (ENDunexplained ), exists. We aimed to investigate the incidence, independent predictors, and clinical impact of ENDunexplained after EVT in patients with acute LVO. Methods: Subjects were selected from the ANGEL-ACT registry. ENDunexplained was defined as ≥4-point increase in the National Institutes of Health Stroke Scale (NIHSS) score between baseline and 24 hours after EVT, without the causes listed above. Logistic regression analyses were performed to determine the independent predictors of ENDunexplained, as well as the association between ENDunexplained and 90-day outcomes assessed by modified Rankin Scale (mRS) score. Results: Among the 1557 enrolled patients, the incidence of ENDunexplained was 4.3% (67/1557). Admission NIHSS ≤8 (OR=6.88, 95% CI 3.86 to 12.26, p<0.001), general anesthesia (OR=3.15, 95% CI 1.81 to 5.48, p<0.001), admission neutrophil to lymphocyte ratio >5 (OR=2.82, 95% CI 1.61 to 4.94, p<0.001), and number of EVT attempts >3 (OR=2.11, 95% CI 1.14 to 3.89, p=0.018) were associated independently with a high risk of ENDunexplained . Furthermore, patients with ENDunexplained were associated with a shift toward worse 90-day outcomes (mRS 5 vs 3, common OR=5.24, 95% CI 3.22 to 8.52, p<0.001). Conclusions: ENDunexplained associated with poor 90day outcomes occurred in 4.3% of patients with acute LVO undergoing EVT. Several independent predictors of ENDunexplained were identified in this study, which should be considered in daily practice to improve acute LVO management. Clinical trial Registration: http://wwwclinicaltrialsgov NCT03370939 .